(untitled) (Società e diritti, 2023)
The author of the contribution, who is also the author of the book Economia umana. La lezione e la profezia di Giuseppe Toniolo: una rilettura sistematica (Milan 2021) - Human Economy. The Lesson and Prophecy of Giuseppe Toniolo: A Systematic Review - reacts to various interventions of economists and jurists, who have reflected on the book in a roundtable. He adds a reflection on the actuality of Toniolo, confronting his economic thinking and that of a contemporary economist, Kate Raworth, whose book, Doughnut Economics: Seven Ways to Think like a 21st-century Economist (London 2017), radically questioned the mainstream economy, advocating a renewal in theory and praxis, such that the economy is well regulated within the incontrovertible demands of the respect for human rights and of the environment. Sorrentino holds that the thought of Toniolo, albeit long marginalized, shows itself to be an ample forerunner of this perspective, and, moreover, offers an ethical anchorage, which recalls the structure of the human being and thereby a recognition of the Transcendent, unpleasant to the dominant culture, but necessary, in order that the same ethical renewal of the economy has a solid foundation and does not dissolve into vague and contrasting subjective ethics.